Study of fast-ion-driven toroidal Alfvén eigenmodes impacting on the global confinement in TCV L-mode plasmas - Mazzi, S.; Vallar, M.; Kumar, U.; Krutkin, O.; Poley-Sanjuan, J.; Simons, L.; Ball, J.; Brunner, S.; Coda, S.; Garcia, J.; Iantchenko, A.; Kazakov, Ye. O.; et al. (Frontiers in Physics, 2023)
Following recent observations of unstable Toroidal Alfvén Eigenmodes (TAEs) in a counter-current Neutral Beam Injection (NBI) scenario developed in TCV, an in-depth analysis of the impact of such modes on the global confinement and performance is carried out. The study shows experimental evidence of non-degradation of ion thermal confinement despite the increasing of auxiliary power. During such an improved confinement period, Toroidal Alfvén Eigenmodes (TAEs) driven by fast ions generated through Neutral Beam Injection (NBI) are found unstable. Together with the TAEs, various instabilities associated with the injection of the fast neutrals are observed by multiple diagnostics, and a first characterization is given. Nonlinear wave-wave couplings are also detected through multi-mode analysis, revealing a complex picture of the stability dynamics of the TCV scenario at hand. The measurements provided by a short-pulse reflectometer corroborate the identification and radial localization of the instabilities. A preliminary, but not conclusive, analysis of the impact of TAEs on the amplitude of the electron density fluctuations is carried out. Local flux-tube gyrokinetic simulations show that the dominant underlying instabilities in the absence of fast ions are Trapped Electron Modes (TEM), and that these modes are effectively suppressed by zonal flows. Attempts to simulate the simultaneous presence of fast-ion driven TAEs and TEM turbulence show that elongated streamers develop up to the full radial extent of the flux-tube domain, thereby invalidating the local assumption and indicating that a global approach is mandatory in these TCV plasmas.